A doubling of atmospheric CO2 mitigates the effects of severe drought on maize through the preservation of soil water. (8th February 2022) - Ripley, B S; Bopape, T M; Vetter, S
Abstract: Background and Aims: Drought limits maize production in many regions of the world, and this is likely to intensify in future. Elevated atmospheric CO2 ( e CO2 ) can mitigate this by reducing stomatal conductance and water loss without reducing yield. The magnitude of this effect depends on the interaction of e CO2 and drought severity, but scarce data collected under severe drought conditions limit predictions of future maize production. Methods: We compared the severe drought × e CO2 responses of six maize genotypes from semi-arid and sub-humid growing regions. Key Results: Genotypic differences were apparent in growth, gas exchange, water relations, grain quality, and biomass at maturity, but the response to e CO2 was consistent. Plants under drought and e CO2 had similar biomass and yield to irrigated plants at ambient CO2 . Reduced stomatal conductance and water loss preserved soil moisture equivalent to 35 mm of rainfall and allowed sustained photosynthesis at higher rates for a longer period after watering stopped. Under irrigation, e CO2 improved maize growth but not grain yield. Conclusions: The results suggest that e CO2 may extend the future land area available to rainfed maize cultivation, but cannot circumvent the absence of seasonal rainfall that restricts maize growth. Elevated CO2 will reduce water requirements of irrigated maize when atmospheric conditions drive high evapotranspiration.